The Safety Tips for ATV Riders (STARs) programme: short-term impact of a school-based educational intervention. Issue 3 (28th November 2014) - Jennissen, Charles A; Peck, Jeffrey; Wetjen, Kristel; Hoogerwerf, Pam; Harland, Karisa K; Denning, Gerene M
Abstract : Background: Since 1985, one-third of all US all-terrain vehicle (ATV)-related injuries and one-quarter of deaths involved victims <16 years of age. ATV safety education of youth could help reduce these tragedies. Objectives: To assess the efficacy of the S afety T ips for A TV R ider s (STARs) school-based programme targeting adolescents. Methods: A survey was anonymously administered before and after the programme to determine demographics, knowledge and reported likelihood of using the information learned. Results: Over 4600 students in 30 Iowa schools participated from November 2010 to April 2013. Initially, 52% knew most ATVs are designed for one rider, 25% knew the recommended vehicle size for their age range and 42% knew riding on Iowa's roads was legal only for agricultural purposes. After the programme, this increased to 92%, 82% and 76%, respectively (p<0.0001 in each case), with 61% of students correct on all three. Better preintervention scores were associated with being males, higher riding frequency and being from isolated rural communities. After the programme, 48% and 32% said they were likely/very likely versus unlikely/very unlikely to use the safety information learned, respectively; younger students, females and infrequent riders reported higher likelihoods. Conclusions: STARs increased short-term ATV safety knowledge and almost half the participants reported they would use the safety information presented. Males and frequent riders seemed more resistant, but some groups that may be more vulnerable to potential ATV crash and injury appeared amenable to the training with higher increases in postprogramme scores and greater intention of improving safety behaviours.